The global fight to develop antipoverty vaccines in the anti-vaccine era - Peter J. Hotez (Taylor & Francis Group, 2018)
Antipoverty vaccines are the vaccines targeting a group of approximately 20 neglected tropical diseases (NTDs), as currently defined by the World Health Organization (WHO). The "antipoverty" moniker refers to the fact that NTDs trap populations in poverty due to their chronic and deleterious effects on child intellect and worker productivity. Therefore, NTD vaccines can be expected to promote both global health and economic advancement. Unfortunately, antipoverty vaccine development has lagged behind vaccines for major childhood infections and pandemic threats, despite evidence for their cost-effectiveness and cost-savings. Currently, the only licensed vaccines for NTDs include those for yellow fever, dengue, and rabies, although several other NTD vaccines for hookworm disease, schistosomiasis, leishmaniasis, and Zika and Ebola virus infections are in different stages of clinical development, while others are at the preclinical development stage. With the exception of the viral NTD vaccines there so far has been minimal industry interest in the antipoverty vaccines, leaving their development to a handful of non-profit product development partnerships. The major scientific and geopolitical hurdles to antipoverty vaccine development are discussed, including a rising antivaccine ("antivax") movement now entering highly populated low- and middle-income countries.